FAKTOR–FAKTOR YANG MEMPENGARUHI FISCAL STRESS DI PROVINSI SUMATERA SELATAN - Yuli Antina Aryani; Sandrayati; R. Rahmat Soleh (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to determine the effect of fiscal decentralization, local revenue and capital expenditure on fiscal stress in South Sumatra Province, which consists of 17 regencies/cities from 2017 to 2021. The sample collection technique in this study is non-probability sampling. This study uses secondary data originating from the website http://e-ppid.bpk.go.id/ in the form of Regional Revenue and Expenditure Budget Realization Reports. The hypothesis testing tool in this study used EVIEWS version 12 software, with the data analysis method used was multiple linear regression analysis method. Based on the results of testing the hypothesis, it can be concluded that fiscal decentralization has a negative effect on fiscal stress, regional original income and capital expenditure have a positive effect on fiscal stress. Keywords: Fiscal Stress, Decentralization, Revenue, Expends